2016
DOI: 10.1097/mca.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Access-site bleeding and radial artery occlusion in transradial primary percutaneous coronary intervention

Abstract: After transradial primary percutaneous coronary intervention, early patent hemostasis and short artery compression times were associated with a higher incidence of local hematomas. The incidence of hematomas was dependent on the use of abciximab, but unrelated to the type of P2Y12 inhibitor used. All hematomas were without clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…14,15 While some studies have reported lower incidence of hematoma, Hromádka et al and Susanu et al reported hematoma in 6.28% and 6.12% patients after TRA-PCI respectively. 16,17 The variation in incidence of hematoma may be due to diversity in definition to define hematoma in different studies, experience of interventionists and size of sheath used to vascular access. However, the sheath size may or may not be the predictor of hematoma, a recent study compared the outcomes of TRA-PCI with sheath versus without sheath, the authors did not reported any significant in incidence of hematoma in sheath and sheath-less PCI groups.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 While some studies have reported lower incidence of hematoma, Hromádka et al and Susanu et al reported hematoma in 6.28% and 6.12% patients after TRA-PCI respectively. 16,17 The variation in incidence of hematoma may be due to diversity in definition to define hematoma in different studies, experience of interventionists and size of sheath used to vascular access. However, the sheath size may or may not be the predictor of hematoma, a recent study compared the outcomes of TRA-PCI with sheath versus without sheath, the authors did not reported any significant in incidence of hematoma in sheath and sheath-less PCI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Výskyt lokálních krvácivých komplikací byl v naší studii nízký a všechny hematomy byly klinicky nevýznamné. V jiné studii z našeho pracoviště [13], jež srovnávala výskyt lokálních komplikací u pacientů s akutním koronárním syndromem s elevacemi úseků ST léčených primární PCI, byl ve skupině pacientů bez abciximabu výskyt hematomu II. stupně 5 % a III.…”
Section: Diskuseunclassified
“…Hromádka et al [11], in this issue of Coronary Artery Disease, explore this issue in part, by describing their experience with 334 consecutive STEMI patients who were treated with transradial PCI at their institution. Although nonrandomized, they had three groups of patients of roughly equal size and similar demographics who received clopidogrel, prasugrel, or ticagrelor.…”
mentioning
confidence: 98%